Extending the Touchscreen Pattern Lock Mechanism with Duplicated and Temporal Codes. (29th November 2016) - Colley, Ashley; Seitz, Tobias; Lappalainen, Tuomas; Kranz, Matthias; Häkkilä, Jonna
Abstract : We investigate improvements to authentication on mobile touchscreen phones and present a novel extension to the widely used touchscreen pattern lock mechanism. Our solution allows including nodes in the grid multiple times, which enhances the resilience to smudge and other forms of attack. For example, for a smudge pattern covering 7 nodes, our approach increases the amount of possible lock patterns by a factor of 15 times. Our concept was implemented and evaluated in a laboratory user test (n = 36 ). The test participants found the usability of the proposed concept to be equal to that of the baseline pattern lock mechanism but considered it more secure. Our solution is fully backwards-compatible with the current baseline pattern lock mechanism, hence enabling easy adoption whilst providing higher security at a comparable level of usability.